The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41567-021-01197-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hall carrier density in the overdoped strange metal regime of cuprate superconductors

Abstract: Efforts to understand the microscopic origin of superconductivity in the cuprates are dependent on knowledge of the normal state. The Hall number in the low-temperature, high-field limit n H (0) has a particular importance because, within conventional transport theory, it is simply related to the number of charge carriers, so its evolution with doping gives crucial information about the nature of the charge transport. Here we report a study of the high-field Hall coefficient of the single-layer cuprates Tl 2 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(138 citation statements)
references
References 52 publications
13
125
0
Order By: Relevance
“…4, interpreted as a sharp nearly twofold drop in carrier density with decreasing p [11]. A similar decrease has been reported by Putzke et al [10] and a very similar drop was observed previously in YBCO [8] and Nd-LSCO [9]. This drop has been identified as a key signature of the pseudogap phase that reveals a transformation of the Fermi surface across p ⋆ , consistent with a change from a large surface containing 1 + p holes to small Fermi pockets containing p holes [32,43].…”
Section: B Bi 2+y Sr 2−x−y La X Cuo 6+δsupporting
confidence: 79%
See 1 more Smart Citation
“…4, interpreted as a sharp nearly twofold drop in carrier density with decreasing p [11]. A similar decrease has been reported by Putzke et al [10] and a very similar drop was observed previously in YBCO [8] and Nd-LSCO [9]. This drop has been identified as a key signature of the pseudogap phase that reveals a transformation of the Fermi surface across p ⋆ , consistent with a change from a large surface containing 1 + p holes to small Fermi pockets containing p holes [32,43].…”
Section: B Bi 2+y Sr 2−x−y La X Cuo 6+δsupporting
confidence: 79%
“…[1,2]inTl 2 Ba 2 CuO 6+δ ), the measured carrier concentration is equal to n H = 1 + p (per CuO 2 plane), and the Sommerfeld coefficient is on the order of 5 mJ mol −1 K −2 [3][4][5][6]. On the other hand, for p p ⋆ , angle-resolved photoemission spectroscopy (ARPES) stud-ies show that the Fermi surface breaks into small nodal "Fermi arcs" [7] and Hall effect measurements then indicate that the carrier concentration drops to n H = p in YBa 2 Cu 3 O y (YBCO) [8], Nd 0.4 La 1.6−x Sr x CuO 4 (Nd-LSCO) [9], and Bi 2+y Sr 2−x−y La x CuO 6+δ (Bi2201) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In reality, the normal state transport properties of all OD cuprates, including Tl2201, are far from conventional. This so-called 'strange metal' regime has three notable characteristics: (i) a ubiquitous non-FL (T -linear) component in the in-plane resistivity ρ ab (T ) at low T [10][11][12], whose coefficient α(0) scales with T c and is consistent with a scattering rate at the Planckian dissipation limit ħ h/τ ∼ k B T [12,13]; (ii) a Hall number n H (0) deduced from the low-T Hall effect that does not follow the expected 'Luttinger' 1 + p line but instead drops monotonically towards p near OP doping [14] and (iii) a H-linear magnetoresistance (MR) at high field strengths [15] that exhibits H/T scaling [16] and is also insensitive to both field orientation and impurity scattering rate [16] (for more details, see the introduction to appendix A).…”
Section: Introductionmentioning
confidence: 62%
“…where the Fermi level ε F crosses a van Hove singularity (vHs) -may result in a Tlinear resistivity down to 0 K [18]. While the two cuprate families considered here are known to host a vHs crossing somewhere in their phase diagram, across the doping region of interest (0.20 < p < 0.30), ε F in LSCO is tuned away from the vHS, while in Tl2201, ε F is tuned towards it [14]. The evolution of the T -linear coefficient with doping in both systems, however, is very similar [12,13].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation